2021
DOI: 10.1002/ecs2.3412
|View full text |Cite
|
Sign up to set email alerts
|

Plant community responses to integrating livestock into a reduced‐till organic cropping system

Abstract: Plant community responses to integrating livestock into a reduced-till organic cropping system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 63 publications
0
20
2
Order By: Relevance
“…For example, analyses of the use of specific inputs are associated with agronomic or economic benefits. Most organic grain farmers still rely heavily on moldboard plowing for tillage, and there is evidence that tillage can undermine the positive benefits of organic management on soil health [47][48][49]. There are significant challenges to managing weeds without synthetic chemicals; possibilities exist for combining cover cropping, mulching, and mechanical methods, but more research is needed in conjunction with farmers to work through unknowns and complications [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, analyses of the use of specific inputs are associated with agronomic or economic benefits. Most organic grain farmers still rely heavily on moldboard plowing for tillage, and there is evidence that tillage can undermine the positive benefits of organic management on soil health [47][48][49]. There are significant challenges to managing weeds without synthetic chemicals; possibilities exist for combining cover cropping, mulching, and mechanical methods, but more research is needed in conjunction with farmers to work through unknowns and complications [15].…”
Section: Discussionmentioning
confidence: 99%
“…There are significant challenges to managing weeds without synthetic chemicals; possibilities exist for combining cover cropping, mulching, and mechanical methods, but more research is needed in conjunction with farmers to work through unknowns and complications [15]. Future research on the use of conservation tillage in the context of organic farming could provide important insights for adapting current systems and improving the environmental footprint of organic corn production [47][48][49]. Likewise, producers use a wide range of purchased products on their organic corn fields, many of which have received little attention from the scientific community [50] and should be further explored in terms of their agronomic and economic benefits for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, organic production relies on diversified crop rotations, cover crops, and tillage to manage soil fertility and pests. Previous studies conducted in this region [10][11][12] determined that the different suites of management practices associated with these systems resulted in distinct weed communities, with an overall increased abundance, species richness, and species diversity, as well as more complex spatial distribution in organic farms than in conventionally managed ones.…”
Section: Introductionmentioning
confidence: 99%
“…One example is the integration of crop and livestock production where targeted grazing is used to terminate cover crops and manage weeds [21]. Previous research indicated that, in the Northern Great Plains, the integration of crop and livestock production in organic systems allows a reduction in tillage intensity [11] but can impact the structure of weed [11,22], invertebrate [23], and soil microbial [24][25][26] communities. Yet, to our knowledge, no study has specifically compared the impact of predicted increased temperature and reduced moisture conditions on weed communities among conventional and organic cropping systems with varying degrees of soil disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…In vineyards, plant cover (usually mown) has become widespread as a viable option to conventional management based on soil tillage, with positive effects such as the improvement of soil properties or the enhancement of biodiversity (Winter et al, 2018;Novara et al, 2019;Guerra et al, 2022), although exhibiting in some cases a reduction on vineyard vigor and yield (Monteiro and Lopes, 2007;Celette and Gary, 2013). The impact of weed management on weed communities has been extensively documented, revealing that management practices such as tillage, herbicide or mowing can exert selective pressure on these communities, altering their composition and/or taxonomic diversity (Doradoand Loṕez-Fando, 2006;Jose-Marıá et al, 2010;Grundy et al, 2011;Larson et al, 2021;Guerra et al, 2022). However, gaps remain on how these management practices might affect plant functional diversity.…”
Section: Introductionmentioning
confidence: 99%